Smartharvest: agriculture IoT-enabled solar irrigation system - Azlan, Muhammad Azfar; Othman, Norhalida; Ismail, Muhammad Asyraf; Muhamad, Nur Amalina (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The SmartHarvest is an innovative solution designed to optimize water management in agriculture using solar energy and IoT technologies. Equipped with solar panels, DHT22 sensors for temperature and humidity, LDRs for light intensity, soil moisture sensors, an ESP32 microcontroller, and DC water pumps, this system autonomously adjusts irrigation based on real-time data, promoting water conservation and improving crop health. The system’s use of solar power makes it eco-friendly, reducing reliance on conventional energy sources and operational costs. It also integrates UV lights to ensure clean water, providing an efficient, sustainable method for irrigation. The invention addresses the pressing need for water-efficient agricultural practices, especially in areas experiencing water scarcity, by providing a solution that reduces waste and enhances productivity. Its socio-economic and environmental impacts include increasing agricultural yields, conserving water, and fostering sustainability. With strong commercialization potential, this system offers an ideal solution for farmers globally, particularly in regions where resources are limited or traditional irrigation methods are inefficient. Its scalability and cost-effectiveness make it a promising tool for both small-scale and large-scale agricultural operations